Pheromone biochemistry - Prestwich, Glenn D.; Blomquist, Gary J. (Academic Press, 1987)
Pheromone Biochemistry covers chapters on Lepidoptera, ticks, flies, beetles, and even vertebrate olfactory biochemistry. The book discusses pheromone production and its regulation in female insects; as well as reception, perception, and degradation of pheromones by male insects. The text then describes the pheromone biosynthesis and its regulation and the reception and catabolism of pheromones. Researchers in the areas of chemistry, biochemistry, entomology, neurobiology, molecular biology, enzymology, morphology, behavior, and ecology will find the book useful.